2021
DOI: 10.3390/nu13103606
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Safe Consumption of Nuts in Terms of the Content of Toxic Elements with Chemometric Analysis

Abstract: Nuts are characterized by high nutritional value and are recommended as a part of a healthy diet. At the same time, toxic elements could also be found in them. In this research, we measured the content of As, Cd, Pb and Hg in a wide variety of edible nuts. To determine the As content, inductively coupled plasma mass spectrometry (ICP-MS) was applied. Cd and Pb were detected by the electrothermal atomic absorption spectrometry analytical technique (ETAAS) with Zeeman background correction, while atomic absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent study demonstrated that exposure to nuts can be hazardous because they contain some toxic elements such as arsenic (As), lead (Pd), and mercury (Hg), but in very low amounts that do not cause any harm to human health. Generally, consuming products with toxic elements above the admissible amount can be threatening to health [8]. Growing interest is nowadays focused on hazelnuts, almonds, and pistachios.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that exposure to nuts can be hazardous because they contain some toxic elements such as arsenic (As), lead (Pd), and mercury (Hg), but in very low amounts that do not cause any harm to human health. Generally, consuming products with toxic elements above the admissible amount can be threatening to health [8]. Growing interest is nowadays focused on hazelnuts, almonds, and pistachios.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, 8% of tested samples exceeded the lead limit, 33% of which were pecans. The remaining studied products were considered safe [ 10 ]. Nevertheless, there are many health benefits associated with adding nuts from verified sources to the diet.…”
Section: Introductionmentioning
confidence: 99%